IDENTIFIKASI BIOMONITORING BAHAYA BAHAN KIMIA PADA PEKERJA INDUSTRI - Pratama Sitorus, Ardiansyah; Susilawati, Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Background: The work environment in both formal and non-formal companies always has risks of danger that can have an impact on both workers and the environment itself. To overcome this impact, it is necessary to monitor bimonitoring so that workers avoid various threats while working. Research Objectives: This study aims to describe the dangers of chemicals through biomonitoring. Research Methods: This study used the literature review method. Literature review is an approach used to collect and analyze relevant information from existing literature sources. Results & Discussion: There are still many industries that are growing rapidly in Indonesia today that have not run according to applicable operational rules. There are still industries that don't understand the regulations that are made, such as the threshold for quality standards for production materials that still exceed the standards and how K3 operational standard management is applied. Conclusion: Based on the results of the research above, it can be concluded that monitoring of chemical hazards in the industry can be done by bimonitoring. There are still industries that exceed their quality standards which can endanger the health of industrial workers.